Ruptured ectopic pregnancy with negative serum beta-human chorionic gonadotropin: a case report and literature review - van der Hock, Sarah; Gibson, Lara; Dhupar, Nita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
A negative urine pregnancy test is commonly used in emergency settings to exclude pregnancy; however, this assumption can be misleading and may delay critical diagnoses. We present a rare case of a ruptured ectopic pregnancy in a 30-year-old female with a serum beta-human chorionic gonadotropin (hCG) level of only 4 IU/l, falsely suggesting the absence of pregnancy. The patient presented with sudden-onset lower abdominal pain, presyncope, and hemodynamic instability. On arrival, she was hypotensive and tachycardic, with clinical and ultrasound findings consistent with massive hemoperitoneum of more than three litres of blood. Despite an initial negative pregnancy test, the patient required emergent laparotomy and right salpingectomy for a ruptured ectopic pregnancy. The patient was resuscitated with blood products and stabilised postoperatively in the intensive care unit before being discharged. This case highlights the limitations of beta-hCG testing in diagnosing ectopic pregnancy, emphasising that low or undetectable levels do not exclude the condition. A comprehensive literature review identified fourteen similar cases of ruptured ectopic pregnancy with negative or low serum beta-hCG levels, illustrating the diagnostic challenges associated with such presentations. Whilst serial beta-hCG monitoring remains a valuable tool, this case underscores the importance of clinical suspicion and point-of-care imaging, particularly transvaginal ultrasound (TVUS), as the primary modality for detecting ectopic pregnancies. Early recognition and intervention are crucial to reducing morbidity and mortality.